INFORMATION AND COMMUNICATION TECHNOLOGIES AS AN INSTRUMENT FOR PRESCHOOL EDUCATION QUALITY IMPROVEMENT - Halyna A. Nazarenko; Tetiana K. Andriushchenko (Інформаційні технології і засоби навчання, 2019)
The article highlights the results of the research on information and communication technologies potential possibilities for preschool education quality improvement. During conceptual-diagnostical, organization-preparational, formational and test-generalizing stages of pedagogical experiment in educational establishments there were created necessary material-technical conditions for effective use of ICT in different spheres of preschool education. The research of pedagogical software required for qualified preschool education and other digital educational resources was carried out. It was provided teachers training to use ICT in organization of preschool education and in personal professional development, as well as created methodological support for the implementation of ICT in sphere of preschool education. It has been proved that the quality of preschool education characterizes both the educational process and its results, reflects the level of achieving the aim and tasks of education, upbringing and development of preschool age children and also the level of fulfillment of teachers’, children’s and their parents’ expectations from the use of ICT in the educational process at preschool educational establishments. This article ascertains a significant potential of ICT in the development of preschool teachers IC-competency, organization of education, upbringing and development of children of the upper preschool age, testifies to the importance of cooperation with parents of preschoolers. It presents the experience of using ICT as a didactic tool, which contributed to a more effective realization of the tasks of the main lines of education, which are defined as a basic component of preschool education: “Child’s personality”, “Child in the society”, “Child in the environment”, “Child in the world of culture”, “Child’s game”, “Child in sensory-cognitive space” and “Child’s speech”. The article reveals the significant potential of the use of information and communication technologies for raising the parental awareness about the quality of educational services in the preschool educational institution, as well as for establishing a partnership between the teaching staff and the parent community on all issues of preschool education.